Detection of Hydroxyproline O-galactoside by LC/MS - Mari Ogawa-Ohnishi; Yoshikatsu Matsubayashi (Bio-Protocol, 2016)
Hydroxyproline (Hyp) O-galactosylation is a plant-specific post-translational modification found in extracellular glycoproteins such as arabinogalactan proteins (AGPs). Hyp O-galactosylation is mediated by Hyp O-galactosyltransferase (HPGT) that catalyzes the transfer of a D-galactopyranosyl residue to the hydroxyl group of Hyp residues of peptides from the sugar donor UDP-α-D-Gal. Here we describe an LC/MS-based method for the detection of Hyp O-galactoside.